Answer:
[tex]f(x)=-4(x-2)(x+7)[/tex]
Or, in standard form:
[tex]f(x)=-4x^2-20x+56[/tex]
Step-by-step explanation:
We can use the factored form of a quadratic equation:
[tex]f(x)=a(x-p)(x-q)[/tex]
Where a is the leading coefficient and p and q are the zeros of the quadratic.
We know that the x-intercepts are at (2, 0) and (-7, 0).
So, let's substitute 2 for p and -7 for q. This yields:
[tex]f(x)=a(x-2)(x+7)[/tex]
Now, we need to determine a.
We know that it passes through the point (1, 32). In other words, if we substitute 1 for x, we should get 32 for f(x). Therefore:
[tex]32=a(1-2)(1+7)[/tex]
We can now solve for a. First, compute:
[tex]32=a(-1)(8)[/tex]
Multiply:
[tex]32=-8a[/tex]
Divide both sides by -8:
[tex]a=-4[/tex]
So, the value of a is -4.
Therefore, our entire equation is:
[tex]f(x)=-4(x-2)(x+7)[/tex]
Notes:
We can expand this into standard form:
[tex]f(x)=-4(x-2)(x+7) \\ f(x)=-4(x^2+5x-14) \\ f(x)=-4x^2-20x+56[/tex]